2020
DOI: 10.3390/metabo10060263
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Folic Acid Supplementation Alone or in Combination with Vitamin B12 in Dairy Cattle during Periparturient Period

Abstract: The periparturient period is the period from three weeks before calving to three weeks post-calving. This period is important in terms of health, productivity and profitability, and is fundamental to successful lactation. During this period, the animal experiences stress because of hormonal changes due to pregnancy and the significant rise in milk production. In addition, a negative energy balance usually occurs, because the demand for nutrients to sustain milk production increases by more than the nutrient su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 75 publications
0
13
0
Order By: Relevance
“…Previous studies reported that moderately extra FA intake can improve the host immune capacity and reduce inflammation and oxidative stress [ 59 61 ]. Our previous results also indicated that for dairy cows, FA supplementation reduces mastitis incidence and promotes milk production [ 4 , 5 ]. In Mac-T cells infected with S. aureus , the results of the present study showed that the expression of genes within ABC transporters [ 62 ] involved with toxin secretion, MAPK signaling pathway [ 63 ] and p53 signaling pathway [ 64 ] related with inflammatory regulation can be influenced by FA treatment through the regulation of lncRNAs.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Previous studies reported that moderately extra FA intake can improve the host immune capacity and reduce inflammation and oxidative stress [ 59 61 ]. Our previous results also indicated that for dairy cows, FA supplementation reduces mastitis incidence and promotes milk production [ 4 , 5 ]. In Mac-T cells infected with S. aureus , the results of the present study showed that the expression of genes within ABC transporters [ 62 ] involved with toxin secretion, MAPK signaling pathway [ 63 ] and p53 signaling pathway [ 64 ] related with inflammatory regulation can be influenced by FA treatment through the regulation of lncRNAs.…”
Section: Discussionmentioning
confidence: 91%
“…Mastitis induced by the contagious pathogen S. aureus and methicillin-resistant S. aureus (MRSA) is still hard to cure [ 3 ]. The host’s inflammatory response is dependent on the different lineages of S. aureus and the immune level of the mammary gland tissue [ 4 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Folic acid (FA) is a B-complex vitamin with the sole biochemical role of mediating the transfer of 1-C units in animals [ 7 ]. FA also has a variety of activities, including regulating neurotransmission and gene expression [ 8 , 9 ]. Folate metabolism appears to have a significant impact on the synthesis of milk proteins in the epithelial cells of mammary glands [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, certain micronutrients may be beneficial and environmentally sound for supporting host immune function [ 13 , 14 , 15 ]. Folic acid (FA) plays a crucial role in the development of mammary gland [ 14 ], and reduces certain inflammation in some species (such as cattle [ 16 ], chicken [ 17 ], and mice [ 18 , 19 ]), as well as cancer risks in mice [ 18 ] and human [ 20 ]. FA supplementation reduces postpartum SCC during the periparturient period and improves production traits in dairy cattle [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%